Leveraging Observations of Security Force Assistance in Afghanistan for Global Operations - Payne, Leslie (RAND Corporation, 2013)
Interviews with Security Force Assistance (SFA) practitioners in Afghanistan reveal insights that can be applied to future global operations. The enduring nature of most challenges that these practitioners face suggests that solutions still remain uncertain. Future SFA missions, such as those envisioned for the U.S. Army's Regionally Aligned Forces, can benefit from the experience gained from SFA in Afghanistan as captured in this report.